Análise in vivo da relação entre hipóxia e estresse oxidativo sobre o desenvolvimente embriofetal do pâncreas de descendentes de ratas diabéticas - Iessi, Isabela Lovizutto [UNESP] (2015)
In diabetic pregnancy, hyperglycemia may impair embryonic development by a combination of hypoxia and oxidative stress. Therefore, we hypothesized that a combination of these factors was involved in the impaired pancreatic development in the offspring. Thus, the objective of the present study was to evaluate maternal oxidative stress and hypoxia status on fetal pancreatic development in hyperglycemic conditions. Wistar rats were randomly assigned into three groups: control (C); mild diabetes (MD) and severe diabetes (SD). Diabetes was induced by the beta-cytotoxic drug (streptozotocin) in rats. The female rats were mated and at days 18 (early period of maximum fetal development) and 21 (at term) of pregnancy the maternal hyperglycemia, hypoxia and oxidative stress markers were evaluated. In the fetus, the pancreatic islets were analyzed. The results showed alterations in pancreatic hormone triad (insulin, glucagon and somatostatin), beta cell marker (PDX-1), proliferation (ki67) and apoptosis (caspase-3), which were more pronounced in the SD group. Furthermore, the morphology of the fetal pancreatic islets was clearly changed. There was a positive correlation between blood glucose, oxidative stress and hypoxia of the mothers and the reduction in the number of islets and number of cells per islet in the fetuses from the diabetic groups. Therefore, oxidative stress and hypoxia induced by maternal hyperglycemia led to impairment of fetal pancreatic development. These observations indicate that a rigid glycemic control in diabetic pregnancy is required to prevent the embryofetal and perinatal complications